Elevated D-dimer as an immediate response to alemtuzumab treatment. (January 2021) - Libertinova, Jana; Meluzinova, Eva; Nema, Eva; Rockova, Petra; Elisak, Martin; Petrzalka, Marko; Mojzisova, Hana; Hammer, Jiri; Tomek, Ales; Marusic, Petr
Alemtuzumab as a treatment of highly active multiple sclerosis causes a rapid decrease in inflammatory activity due the lysis of immune cells. Subsequent cytokine release determines the infusion-associated reaction that is a frequent adverse event of alemtuzumab treatment. Recently, serious cardiovascular and thrombotic adverse reactions following alemtuzumab infusion have been described. In our study, the dynamics of coagulation parameters were analyzed in 13 multiple sclerosis patients treated with alemtuzumab. An immediate, significant increase in the level of D-dimer was observed after the first administration of alemtuzumab. This observation provides evidence of coagulation activation and the potential risk of thrombotic complications with this therapy. Prophylactic low molecular weight heparin pretreatment maybe considered in patients receiving alemtuzumab.